2007
DOI: 10.1111/j.1471-0307.2007.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cholesterol removal from cream using β‐cyclodextrin cross‐linked with adipic acid

Abstract: The present study was carried out to optimize the different conditions for cross‐linked β‐cyclodextrin (β‐CD) using adipic acid on cholesterol removal in cream. Different factors were β‐CD concentration, mixing temperature, mixing time and mixing speed. Cross‐linked β‐CD was prepared with adipic acid. When the cream was treated with 10% cross‐linked β‐CD, cholesterol removal was the highest at 90.7%, which was not significantly different from treatments with 15% and 20% cross‐linked β‐CD. Cholesterol removal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 25 publications
11
57
0
Order By: Relevance
“…The acid value of camel hump fat increased when treated with b-CD at 30°C for 1.5 h; that might be caused by the elevated inclusion of b-CD by cholesterol in comparison to free fatty acids, because cholesterol was effectively removed from camel hump fat at this temperature (data not shown). Similar results are shown by Han et al (2007) who explored the optimum conditions for cholesterol removal from butter under the addition of b-CD cross-linked with adipic acid. When butter was treated with 10% cross-linked b-CD cholesterol removal was highest at 90.7%, which was not significantly different from the results after treatments with 15 or 20% cross-linked b-CD.…”
Section: Effect Of Ratio Of Camel Hump Fat To Water On Reduction Of Csupporting
confidence: 66%
See 1 more Smart Citation
“…The acid value of camel hump fat increased when treated with b-CD at 30°C for 1.5 h; that might be caused by the elevated inclusion of b-CD by cholesterol in comparison to free fatty acids, because cholesterol was effectively removed from camel hump fat at this temperature (data not shown). Similar results are shown by Han et al (2007) who explored the optimum conditions for cholesterol removal from butter under the addition of b-CD cross-linked with adipic acid. When butter was treated with 10% cross-linked b-CD cholesterol removal was highest at 90.7%, which was not significantly different from the results after treatments with 15 or 20% cross-linked b-CD.…”
Section: Effect Of Ratio Of Camel Hump Fat To Water On Reduction Of Csupporting
confidence: 66%
“…However, cholesterol removal was significantly influenced by the mixing temperature, the mixing time, and the mixing speed. Han et al (2007) suggested that an excess of b-CD may compete with itself binding cholesterol molecules, resulting in reduced cholesterol removal from the sample.…”
Section: Effect Of Ratio Of Camel Hump Fat To Water On Reduction Of Cmentioning
confidence: 99%
“…In recent years, a number of studies have indicated that cholesterol removal from dairy products such as milk, cream, butter, lard and cheese was most effectively achieved by powder β-cyclodextrin (β-CD) treatment Han et al, 2007;Kim et al, 2005Kim et al, , 2006Kim et al, , 2008Lee et al, 2007). β-CD is a cyclic oligosaccharide composed of α (1→4) linkages of seven glucose units.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed a method using β-CD covalently attached on glass surface which can be removed from ghee after cholesterol extraction and can be applied in repeated cycles after socking in acetic acid and butanol mixture as described by some workers Han et al 2007). β-CD immobilized on glass beads surface was applied for cholesterol reduction from ghee repeatedly 10 times and HPLC results show that there was almost no change in cholesterol reduction efficiency.…”
Section: Stability and Repeated Use Of β-Cd Functionalized Glass Surfacementioning
confidence: 99%
“…It has a cavity at the centre of its molecular arrangement, which can form a non-covalent bonding with many molecules having phenyl ring by formation of a reversible host-guest complex (Reddy et al 2001;Han et al 2007). β-CD is non-toxic, edible, non-hygroscopic and chemically stable.…”
Section: Introductionmentioning
confidence: 99%